2022
DOI: 10.3389/fsoc.2022.991219
|View full text |Cite
|
Sign up to set email alerts
|

Swedish experts' understanding of active aging from a culturally sensitive perspective – a Delphi study of organizational implementation thresholds and ways of development

Abstract: BackgroundInternational migration and aging populations make for important trends, challenging elderly care regimes in an increasingly globalized world. The situation calls for new ways of merging active aging strategy and cultural sensitivity. This study aim to illuminate the gap between cultural sensitivity and active aging to identify perceived thresholds by Swedish municipal officials in the understanding of older late-in-life-immigrants situation.MethodsDelphi methodology in three rounds. Twenty-three per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…On the other hand, when the VLGs are hard to achieve, as with the vignettes of Rima and Hannah, the professionals focus on fixed factors rather than personal preferences to understand the VLGs. These results align with Johansson et al’s (2022) study where professionals in decision-making positions described a wish to base decisions on individual preferences, but began focusing on fixed cultural factors as the older adults’ needs became more complex. Thus, it is argued that cultural sensitivity supported by the WTH is a viable path forward to balance between the othering risk (see Torres, 2006 ) and individual preferences (see Johansson et al, 2021 ).…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, when the VLGs are hard to achieve, as with the vignettes of Rima and Hannah, the professionals focus on fixed factors rather than personal preferences to understand the VLGs. These results align with Johansson et al’s (2022) study where professionals in decision-making positions described a wish to base decisions on individual preferences, but began focusing on fixed cultural factors as the older adults’ needs became more complex. Thus, it is argued that cultural sensitivity supported by the WTH is a viable path forward to balance between the othering risk (see Torres, 2006 ) and individual preferences (see Johansson et al, 2021 ).…”
Section: Discussionsupporting
confidence: 80%
“…Experts clarified the content of the knowledge that healthcare professionals should have to work effectively with diverse populations. The most dominant content related to social determinants of health, social and cultural factors influencing health, and knowledge of the various cultures [16,17,[28][29][30][31][32][33][34][35][36][37]. Other studies highlighted the importance of having knowledge of more aspects.…”
Section: Knowledge Of Diverse Social and Cultural Contextsmentioning
confidence: 99%
“…They also need to develop the competency to critically self-reflect. Apart from general self-reflection [16,26], this competency involved reflection on own beliefs and ideas [16,32], biases, prejudice, stereotypes [17,32,33], practices, behaviours, habits, and contexts [17]. While self-reflection has been identified as a necessary competency for healthcare professionals, it was Hordijk et al's [16] study that found that critical reflection on one's own beliefs was the behaviour that achieved the highest score of consensus among experts.…”
Section: Knowledge Of Own Culture and Critical Reflection On Own Beli...mentioning
confidence: 99%
See 2 more Smart Citations